2019
DOI: 10.1002/2050-7038.12306
|View full text |Cite
|
Sign up to set email alerts
|

An efficient induction motor design for performance intensification using magnet software

Abstract: Summary In this research, a novel three‐phase 2.2 kW squirrel‐cage induction motor is designed in such way that the stator is constructed in a combination of magnets and coils and also the traditional aluminum rotor bar changed as copper rotor bar in the design. Therefore, the magnet should give additional repulsion for rotating the rotor hence reducing the input current. The simulation of novel designed induction motor is done by magnet software. Finite element approach gives accurate computations of the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…On the other hand, it is found that when the thickness of the laminations making up the stator package of a 0.37 kW three-phase induction motor is reduced, the efficiency increases by 1.4% and the power losses decrease [16]. In another study to improve the performance characteristics of a cage-rotor induction motor, an improved design was developed [17]. In it, a combination of magnets and coils is used for the stator, and the aluminum rotor is replaced by a copper one.…”
Section: Increasing the Energy Efficiency Of Induction Motor Drivesmentioning
confidence: 99%
“…On the other hand, it is found that when the thickness of the laminations making up the stator package of a 0.37 kW three-phase induction motor is reduced, the efficiency increases by 1.4% and the power losses decrease [16]. In another study to improve the performance characteristics of a cage-rotor induction motor, an improved design was developed [17]. In it, a combination of magnets and coils is used for the stator, and the aluminum rotor is replaced by a copper one.…”
Section: Increasing the Energy Efficiency Of Induction Motor Drivesmentioning
confidence: 99%
“…The advantages of simple structure, convenient maintenance, relatively cheap, and easy weak magnetic control provide a broad application perspective for the traditional induction motor. However, its service life and work efficiency are reduced by the problems of mechanical friction and heating 1‐4 . A bearingless induction motor(BL‐IM) has changed the support mode of the traditional motor rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Electric motor driven systems convert nearly half of worldwide electric energy in mechanical energy 6 . Relevance on the design of high‐efficiency and robust operation strategies for the induction machine, with a significant reduction of energy consumption, can be thus inferred 7 . Variable frequency control drives for extra‐large induction motors play an important role for efficient use of the energy 8 .…”
Section: Introductionmentioning
confidence: 99%